2008
DOI: 10.1002/gps.2090
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about quality of life in dementia? A review of the emerging evidence on the predictive and explanatory value of disease specific measures of health related quality of life in people with dementia

Abstract: While in other illnesses there may be simple association between HRQL and an easily measurable clinical variable, in dementia this is not so. There are now instruments available with which to measure disease-specific HRQL directly in clinical trials and other studies that can yield informative data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

40
326
7
14

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 265 publications
(387 citation statements)
references
References 56 publications
40
326
7
14
Order By: Relevance
“…Quantitative studies on self-reported, health-related quality of life (HRQL) (see Banerjee et al 2009, for a review) have revealed little or no statistically significant relationship between severity of cognitive impairment and HRQL. Likewise, longitudinal studies have demonstrated that patterns of self-reported HRQL did not match downward curves of cognitive outcomes (Missotten et al 2007;Selwood et al 2005).…”
Section: Perceptions Of Consequencesmentioning
confidence: 99%
“…Quantitative studies on self-reported, health-related quality of life (HRQL) (see Banerjee et al 2009, for a review) have revealed little or no statistically significant relationship between severity of cognitive impairment and HRQL. Likewise, longitudinal studies have demonstrated that patterns of self-reported HRQL did not match downward curves of cognitive outcomes (Missotten et al 2007;Selwood et al 2005).…”
Section: Perceptions Of Consequencesmentioning
confidence: 99%
“…Selv om flere proxybaserte studier finner en signifikant sammenheng mellom adferd og livskvalitet, ser man i studier hvor personen med demens selv har gitt opplysninger om sin livskvalitet, at denne sammenhengen minsker eller forsvinner (29,39,40). Dette kan ha sammenheng med redusert innsikt i egen situasjon, men kan også vaere et uttrykk for at adferd som pleiepersonell opplever som problematisk, ikke er det for personen med demens (8,41).…”
Section: Metodeunclassified
“…I våre analyser er kjønn ikke signifikant korrelert med livskvalitet. Dette er i samsvar med andre studier (5,8,17). Sammenhengen mellom alder og livskvalitet er uklar i vår studie.…”
Section: Metodeunclassified
See 2 more Smart Citations